2014
DOI: 10.19182/bft2014.320.a20542
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation et variabilité génétique de la croissance de <em>Liquidambar styraciflua</em> L. de l'essai de provenances à Mandraka, Madagascar

Abstract: Liquidambar styraciflua ou copalme d'Amérique est une espèce feuillue originaire du Sud-Est des États Unis d'Amérique et de l'Amérique Centrale. L'espèce possède un comportement remarquable en plantation et les propriétés de son bois en font un matériau à usage multiples. En 1986, dans le cadre d'un essai international de provenances de Liquidambar styraciflua, le Commonwealth Forestry Institute (CFI) d'Oxford a diffusé dans plusieurs pays (Brésil, Mexique, Madagascar) des graines de treize provenances récolté… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The higher performance of the three morphotypes (Nls, MaLs and ZLs) could be explained by the fact that their individuals are more tolerant to environmental conditions. This is in line with other findings on others plants especially studies of Yélémou et al (2007) on Piliostigma reticulatum and those of Rakotovololonalimanana et al (2014) on Liquidambar styraciflua L. These studies reported that the observed main growth difference among plants depends on their ability to adapt to environmental conditions. The lower performance for MLs as compared to the other treatments was suggested by literature evidence that it could be as a result of the plants low adaptation capacity to the local environmental conditions.…”
Section: Discussion 41 Overall Variation Of the Plant Growth Patternssupporting
confidence: 92%
“…The higher performance of the three morphotypes (Nls, MaLs and ZLs) could be explained by the fact that their individuals are more tolerant to environmental conditions. This is in line with other findings on others plants especially studies of Yélémou et al (2007) on Piliostigma reticulatum and those of Rakotovololonalimanana et al (2014) on Liquidambar styraciflua L. These studies reported that the observed main growth difference among plants depends on their ability to adapt to environmental conditions. The lower performance for MLs as compared to the other treatments was suggested by literature evidence that it could be as a result of the plants low adaptation capacity to the local environmental conditions.…”
Section: Discussion 41 Overall Variation Of the Plant Growth Patternssupporting
confidence: 92%